OPTIMIZATION OF GLYSEROL TERT-BUTIL ETER PROCESS SYNTHESIS AS A BIODIESEL ADDITIVE - Dwi Setyaningsih, Sri Yuliani dan Amri Solechan (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACT Methyl esters of fatty acids, also known as biodiesel, made from transestherification of vegetable oil with methanol, have shown a lot of promise as alternative diesel fuels. However, biodiesel has some weaknesses that is poor of cold flow properties which can be a problem in temperate climate. Glycerol, as a by product of biodiesel process, can be synthesized become glycerol tert-butyl ether (GTBE) that can improve biodiesel cold flow properties. Etherification of glycerol with tert-butyl alcohol (TBA) catalyzed by bentonite was studied by influence of reaction time, temperature, and amount of catalyst. Central composite rotatable design (CCRD) was used to determine limitations, levels  for each factor, and the experimental design. Minimum level for reaction time was 6 hours and the maximum level was 10 hours. Minimum level for temperature was 60ºC and the maximum level was 80ºC. Minimum level for amount of catalyst was 2.5% and the maximum level was 7.5%. Total GTBE  yields was in the range of 8,958.99 ppm to 265,488.83 ppm. Optimal condition for syntheses GTBE was predicted at 4.9 hours of reaction time, 66.2ºC of reaction temperature, and 9.7% of catalyst with the yield after verification was 962,092.20. GTBE that has been  synthesized could reduce cloud point and pour point biodiesel by 3°C.  Keywords: biodiesel, etherification, glycerol tert-butyl ether (GTBE), optimization